Design, synthesis and photophysical properties of D1-A-D2-A-D1-type small molecules based on fluorobenzotriazole acceptor and dithienosilole core donor for solution processed organic solar cells. (September 2016) - Keshtov, M.L.; Godovsky, D. Yu; Kuklin, S.A.; Lee, J.; Kim, J.; Lim, B.; Lee, H.K.; Biswas, Subhayan; Koukaras, E.N.; Sharma, G.D.
Abstract: Two small molecules denoted asK2 andK3 containing fluorine atoms at different positions of benzotriazole, with linear D1-A-D2-A-D1 configuration based on dithienosilole and fluorobenzotriazole as donor and acceptor materials, were designed and synthesized for small molecule organic solar cells. Their optical and electrochemical properties were investigated. We have used these small molecules as electron donor along with the [6, 6]-phenyl C60 butyric acid methyl ester or [6, 6]-phenyl C71 butyric acid methyl ester as electron acceptor for the fabrication of solution processed organic bulk heterojunction solar cells. High power conversion efficiency values of 6.01% and 4.57% were obtained for devices based onK2 :PC71 BM andK3 :PC71 BM active layers with optimized donor to acceptor weight ratios and processed with a two step annealing treatment. The efficiency of solar cells based on small molecules can be increased considerably by careful engineering and optimization of molecular structure of the blended film morphology. Graphical abstract: PCE values of 6.01% and 4.57% were obtained for devices based onK2 :PC71 BM andK3 :PC71 BM active layers with optimized donor to acceptor weight ratios and processed with a two step annealing treatment (thermal annealing and subsequent solvent vapor annealing). Highlights: Synthesized two small molecules denoted asK2 andK3 . Contains fluorine atoms at different positions of benzotriazole. Employed as donor for BHJ organic solar cells. PCE values of 6.01% and 4.57% achieved optimized K2:PC71BM and K3:PC71BM active layer.